2011
DOI: 10.1007/s11547-011-0687-4
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric analysis of the aneurysmal sac with computed tomography in the follow-up of abdominal aortic aneurysms after endovascular treatment

Abstract: CT volume analysis is an accurate and reproducible modality for the follow-up of abdominal aortic aneurysms after EVAR. At early follow-up, contrast-enhanced CT remains mandatory to identify small endoleaks. For later follow-up, volumetric analysis would eliminate the need for contrast material in asymptomatic patients with stable or decreasing aneurysm volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…For some patients, measurement of AAA volume is more sensitive than diameter measurements in detecting subtle changes in AAA size [9][10][11][12]. Investigators have suggested different ways to implement AAA volume measurement in the followup of patients after EVAR [7][8][9][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For some patients, measurement of AAA volume is more sensitive than diameter measurements in detecting subtle changes in AAA size [9][10][11][12]. Investigators have suggested different ways to implement AAA volume measurement in the followup of patients after EVAR [7][8][9][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The pEL2 are known to be associated with AAA expansion in about 70% of cases after 5 years of FU, which can be interpreted as a surrogate for continued risk of rupture. 12 , 13 , 21 24 Interestingly, although AAA expansion has been reported frequently in the presence of pEL2, increased rates of secondary ruptures and increased AAA-related mortality are scarcely reported in the literature. 24 , 25 , 13 To further complicate the decision-making process in clinical practice, reinterventions for EL2 can be technically challenging with only moderate clinical success rates on the patients’ side and a financial burden on the public health side.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with previous studies and demonstrate a well-selected patient cohort, with strict thresholds for the declaration of AAA expansion and according to interobserver-validated measurements that pEL2 is associated with AAA expansion over time. 4 , 5 , 12 , 13 , 21 , 22 To address confounding factors that influence AAA expansion following EVAR, the groups under investigation in this study were matched for age and gender, which are two known factors that influence the rate of sac expansion. Furthermore, the groups were also comparable in key anatomic criteria, namely, AAA neck morphology and AAA diameter, which also represent factors that are known to be associated with a higher risk of AAA expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation